Inhibition of PI3K pathway increases immune infiltrate in muscle-invasive bladder cancer. (4th May 2019) - Borcoman, Edith; De La Rochere, Philippe; Richer, Wilfrid; Vacher, Sophie; Chemlali, Walid; Krucker, Clémentine; Sirab, Nanour; Radvanyi, Francois; Allory, Yves; Pignot, Géraldine; Barry de Longchamps, Nicolas; Damotte, Diane; et al.
ABSTRACT: Although immune checkpoint inhibitors have shown improvement in survival in comparison to chemotherapy in urothelial bladder cancer, many patients still fail to respond to these treatments and actual efforts are made to identify predictive factors of response to immunotherapy. Understanding the tumor-intrinsic molecular basis, like oncogenic pathways conditioning the presence or absence of tumor-infiltrating T cells (TILs), should provide a new rationale for improved anti-tumor immune therapies. In this study, we found that urothelial bladder cancer from human samples bearing PIK3CA gene mutations was significantly associated with lower expression of a defined immune gene signature, compared to unmutated ones. We identified a reduced 10-gene immune gene signature that discriminates muscle-invasive bladder cancer (MIBC) samples according to immune infiltration and PIK3CA mutation. Using a humanized mouse model, we observed that BKM120, a pan-PI3K inhibitor, significantly inhibited the growth of a human bladder cancer cell line bearing a PIK3CA mutation, associated to increased immune cell infiltration (hCD45+). Using qRT-PCR, we also found an increase in the expression of chemokines and immune genes in PIK3CA- mutated tumors from mice treated with BKM120, reflecting an active immune infiltrate in comparison to untreated ones. Moreover, the addition of BKM120 rendered PIK3CA -mutated tumors sensitive to PD-1 blockade. Our results provide a relevant rationale for combination strategies of PI3K inhibitors with immune checkpoint inhibitors to overcome resistance to immune checkpoint inhibitors.